Hubungan Gaya Pembelajaran Dengan Pencapaian Pelajar Dalam Mata Pelajaran Bahasa Arab Komunikasi di Maktab Mahmud, Alor Setar, Kedah - Kamsani, Md. Saad (2012)
The objectives of the study are to examine the relationship between the students’ learning styles and their achievement in the Communicative Arabic language subject and whether gender plays a role in the strategy chosen. The findings would allow the instructors to plan a more effective learning strategy in learning Communicative Arabic Language. This, in turn, would help arrest the decline of students’ achievement in the second language. 174 respondents were selected randomly from the Form Four classes of Maktab Mahmud, Alor Setar, Kedah for this study. The instrument used to measure the students’ learning style preferences is the ‘Inventori Gaya Pembelajaran’ which is adapted from ‘Perceptual Learning Style Preference Questionnaire’ by Reid which was constructed in 1987. The conceptual frame work for this study is the Dunn and Dunn Model (1978). The statistical procedures used in this quantitative study are t-test and Pearson correlation analysis, and the results are descriptive and inferential. Analysis of the data was carried out using the SPSS. The findings show that the high achievement group of students in the Communicative Arabic Language has effectively used the auditory learning style than the low achievement group. The preferences of female students for visual, kinesthetic, analytic and reflective learning styles than male students reflects the females’ higher achievement in the subject than the males who have less preferences towards the learning styles mentioned. The Pearson correlation analysis result indicated that many students have problems adapting to auditory learning styles. Finally, the study suggests that students should combine and utilize all the various learning styles element in learning the Communicative Arabic Language subject and apply more relevant techniques through the auditory learning style.